EVALUASI PROGRAM KELUARGA SEHAT DENGAN PENDEKATAN KELUARGA (PIS-PK) PADA MASYARAKAT PESISIR UNTUK MENINGKATKAN PELAYANAN KESEHATAN DI WILAYAH PUSKESMAS MEDAN BELAWAN - Susilawati Susilawati; Dini Aprilliani Situmorang (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2023)
Empowerment of coastal communities is an important effort in improving welfare and health services in the region. One effective approach in empowering coastal communities is through the implementation of the Healthy Family Program with a family approach (PIS-PK). The Healthy Family Program is a program that focuses on health promotion, disease prevention, and increasing access to health services for coastal communities. The family approach in this program recognizes the important role of the family as the smallest unit in society and promotes active participation of the family in health-related decision making. Through PIS-PK, coastal communities are encouraged to become agents of change in maintaining and improving the health of their families and communities. This program involves training, health education, and social support to increase public knowledge and awareness about the importance of good health practices. In addition, PIS-PK also focuses on disease prevention by prioritizing a healthy lifestyle, such as a balanced diet, sufficient physical activity, and clean and healthy living habits. This program also provides better accessibility to health services, both through improving health facilities in coastal areas and through advocating for affordable and quality health services. With the implementation of the Healthy Family Program with a family approach (PIS-PK), it is hoped that there will be an increase in sustainable health services in coastal communities. Communities will become more aware of the importance of health and play an active role in maintaining family and community health. In addition, empowering coastal communities can also reduce health disparities between coastal areas and other areas. Therefore, there is a need for strong support from the government, non-governmental organizations and other stakeholders in the implementation of the Healthy Families Program with a family approach (PIS-PK). This support includes the allocation of adequate resources, training of health workers, advocacy of supportive health policies, and active community participation in program planning and evaluation. Thus, PIS-PK can be a concrete step in improving health services and welfare of coastal communities. This program not only provides immediate health benefits to the community, but also produces positive changes in people's mindset and behavior related to health